Different Nucleation Mechanisms during Atomic Layer Deposition of HfS2 on Cobalt Oxide Surfaces - Fickenscher, Georg; Sidorenko, Nikolai; Mikulinskaya, Kira; Libuda, Jörg (Advanced Materials Interfaces, 2024)
The atomic layer deposition (ALD) of HfS2 is investigated on atomically defined CoO(100) and CoO(111) surfaces under ultrahigh-vacuum (UHV) conditions. The ALD process is performed by sequential dosing of the precursors tetrakis(dimethylamido)hafnium (TDMAH) and deuterium sulfide (D2S) separated by purging periods. The growth and nucleation reactions are monitored by in situ infrared reflection absorption spectroscopy (IRAS). HfS2 films nucleate and grow on both cobalt oxide surfaces, despite the fact that CoO(100) lacks acidic protons and CoO(111) exposes only very few OH groups at defects. On these OH-free or OH-lean surfaces, the nucleation step involves a Lewis acid-base reaction instead. The stoichiometry of the ─Hf(NMe2)x nuclei changes during the first ALD half cycle. On CoO(100), the split-off ligands bind as ─NMe2 to surface cobalt ions. The nucleation on CoO(111) is more complex and the split-off ligands undergo dehydrogenation to form various surface species with C═N double and C≡N triple bonds and surface OH. These findings reveal a new nucleation mechanism for ALD in the absence of acidic protons and show that other factors such as Lewis acidity, surface structure, and surface reactivity must also be considered in the nucleation event.
CRIS-Team Scopus Importer:2024-06-21
Keywords: atomic layer deposition; cobalt oxide; HfS; infrared reflection absorption spectroscopy; Lewis acid–base reaction